(untitled) (Bangladesh Journal of Physics, 2026)
This study investigates the effect of annealing temperature (AT) on the structural and optical properties of CFTS (Cu2FeSnS4) thin films fabricated via the spin coating technique on glass substrates. The films were annealed at 300 °C, 340 °C, and 380 °C. X-ray diffraction confirms that all films crystallize in the kesterite structure, with higher AT enhancing crystallinity, increasing crystallite size, and reducing lattice defects. Optical characterization reveals that absorbance, absorption coefficient ( 104 cm-1), and refractive index increase with AT, while the optical band gap shows a decreasing trend. Optical conductivity also rises, indicating improved charge carrier mobility and electronic response. These findings demonstrate that optimized annealing enhances the structural and optical quality of CFTS films, confirming their potential as efficient absorber layers for thin-film solar cells. Bangladesh Journal of Physics, Vol. 32, Issue 2, pp. 43 – 52, December 2025